Transient Numerical Study to Determine the Effect of Inlet Angle Variation on Flow Conditions inside a Circular Aquaculture Tank - Ahmad Wali El-Haq; Ryan Anugrah Putra (Jurnal Inotera, 2023)
Seeing how great the contribution and potential of the aquaculture sector to the fulfillment of food for the people of Indonesia, the development of aquaculture including the Recirculating Aquaculture System (RAS) is very important to be carried out intensively. An important aspect that should be considered for the development of RAS is maintaining water quality as the main medium of cultivation. Optimization of the aquaculture tank is an effort that can be conducted to achieve this goal. A transient numerical study to determine the effect of inlet angle variation on flow conditions inside a circular aquaculture tank was conducted to assess the optimum geometry for the application. Single-phase CFD simulations using the k-ω SST turbulent model were carried out to evaluate the effect of inlet nozzle angle variations. Three angle variations 0°, 45°, and 90° were selected and the resultant fluid flow conditions were analyzed. From the CFD results, it can be known that the optimum condition for the circular aquaculture tank is achieved for the angle 0° among the tested angle in this present study.